Exploring the mediation of perceived social support and psychological capital on academic stress and student burnout among undergraduate students - Gebregergis, Werede Tareke; Csukonyi , Csilla (American Journal of STEM Education, 2024)
The increasing prevalence of stress and burnout among college students has become widespread, and addressing these issues has long been a critical concern for college communities. Given this context, the study was carried out to explore whether social support and psychological capital function as protective factors against academic stress and burnout. The sample consisted of 448 college students who completed a set of measures assessing their academic stress, burnout, social support, and psychological capital. Hierarchical multiple regression and the PROCESS macro for SPSS were used for data analyses. The results revealed that academic stress was significantly related to academic burnout. Further, social support and psychological capital partially mediated the relationship between academic stress and burnout. The findings underscore the importance of addressing academic stress as a key risk factor for burnout and highlight the essential roles of perceived social support and psychological capital in promoting students’ mental health.